Influence of impurities in polygonization of fcc metals of low stacking fault energy - Bebczuk de Cusminsky, Juana (1977)
Several studies performed on metal polygonization [1-3] indicate that impurities lock the dislocations and prevent their motion during a thermal treatment of previously deformed crystals. Nevertheless, the study made on polygonization of Cu showed contradictory results. Young [4, 5] and Wei et al. [6] observed polygonization in OFHC Cu, but not in 99.999% Cu, and pointed out that polygonization in Cu is very slow and occurs upon prolonged annealing at temperatures near the melting point. Seeger and Schoeck [7, 8] suggested that, in metals of low stacking fault energy like Cu, Ag and Au, the dislocations would be extended into widely separated partials, and thus climbing would be difficult. The fact that polygonization has been observed [4, 5] in OFHC Cu, but not in 99.999% Cu, was explained by considering that impurities tend to allow the partial dislocations to recombine. More recently, French workers [9 - 13], showed that pure Cu polygonizes more easily than impure. In order to clarify the effect of impurities in climbing of the extended dislocations in fcc metals, and to find the effect of the stacking fault energy, the present study was carried out in Cu and Ag crystals.